Analysis of Risk Tolerance, Overconfidence, Loss Aversion, and Herd Behavior on Investment Decisions Mediated by Financial Literacy - Nurastuti, Preatmi; Rakhmat, Adrianna Syariefur; Madiyoh, Abdulhakim (Institut Bisnis dan Informatika Kesatuan, 2025)
This study examines the influence of risk tolerance, overconfidence, loss aversion, and herd behavior on investment decisions mediated by financial literacy. The conceptual framework is based on behavioral finance, prospect, and planned behavior theories. Data were collected from 256 university students who participated in this study. The research instrument was a structured questionnaire designed to measure risk tolerance, overconfidence, loss aversion, herd behavior, financial literacy, and obtain information related to respondents’ investment decisions. After the primary data were collected, SmartPLS analysis was conducted to generate a feasible model. PLS-SEM analysis determined its validity and reliability. Two sub-models were also used: a measurement model (outer model) and a structural model (inner model), both of which play a crucial role in understanding the interactions between the variables in the study. The main finding of this study is that risk tolerance, overconfidence, and loss aversion significantly influence investment decisions, both directly and indirectly through financial literacy as a mediating variable, thereby confirming the four proposed hypotheses. This study shows that the level of risk tolerance, overconfidence, loss aversion, and group behavior partially increase their role in shaping investment preferences and decisions when mediated by financial literacy.